Sosialisasi dan Edukasi Perilaku Anti Korupsi Bagi Siswa Sekolah Dasar dalam Upaya Pencegahan dan Pemberantasan Tindak Pidana Korupsi di Dusun Pranan - Agung Nugroho; Amalia Hasnawati; Arsi Ciptaning Tyas; Risky Aji Yudha Wiratama (Universitas Negeri Semarang, 2026)
Corruption has now developed into a deep-rooted social problem in Indonesia. Overcoming corrupt behavior can be done through preventive measures. Prevention and eradication of corrupt behavior is not only the responsibility of law enforcement, but also requires participation from all levels of society, including students. Efforts to eradicate corruption place the role of society not in legal action which is the domain of law enforcement, but in developing an anti-corruption culture in the community. The introduction of an anti-corruption culture needs to be done early on, one of which is through the world of education, starting from Elementary School (SD) to High School (SMA). Departing from this statement, the UNNES GIAT 9 group offers a solution in the form of implementing anti-corruption socialization specifically for elementary school children with the aim of forming anti-corruption souls from an early age. The service methods applied in this activity are observation, socialization, and documentation. This method was chosen because it is considered very effective. Ultimately, with the implementation of this socialization, anti-corruption souls can also be formed among children from an early age, especially in Pranan Village.